PENINGKATAN PROFESIONALISME GURU MELALUI PELATIHAN PEMBELAJARAN BERBASIS LEARNING MANAGEMENT SYSTEM (LMS) DENGAN APLIKASI EDMODO BAGI PARA GURU BIDANG KEJURUAN DI SMK MULTI MEKANIK MASMUR PEKANBARU - Finanta Okmayura; Noverta Effendi; Adlian Jefiza (LPPM UMRI, 2018)
The field mastery of technology, especially in the field of Information and Communication Technology, is one of the obligations for teachers to improve their competence. But at this time the teachers are still applying the conventional teaching model, for example when the teacher stands in front of the class then explains about the subject. This is good for students who pay attention what the material explained by teacher, but if there is the student who can not attend that class they will be missed the lesson. One of some ways to overcome this problem needs for an additional mechanism as an additional learning media as teacher assistants, especially for vocational teachers in SMK Masmur Pekanbaru. The additional learning media is a Learning Management System (LMS) based learning. LMS is a form of web-based computer software, by uploading it to the internet, the e-learning system will be accessible anywhere and anytime. This training is based on LMS where the teachers will use the Edmodo application. By using Edmodo, the teachers have more rights to regulate who can join the group that is created, can control the activities of their students, and can directly assess the tasks. It is expected that LMS-based learning with Edmodo application to be able to improve teachers professionalism and make the learning process in the classroom more efficient than before